1996
DOI: 10.1002/anie.199628011
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (–)‐Epothilone A

Abstract: 21] Solutions of 6 and 7 (each 100 p~ at start) were titrated with a solution of sonicated calf thymus DNA, and the resulting spectral profiles were measured. For each run, volume changes due to DNA additions were taken into account in the calculation of the [DNA]:[drug] ratio. DNA concentration is given in pairs of base pairs (pbp), as this unit represents the minimum structural motif required for intercalation (Table 1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
80
0
1

Year Published

1998
1998
2001
2001

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 221 publications
(81 citation statements)
references
References 14 publications
0
80
0
1
Order By: Relevance
“…Recently, the total synthesis of epothilones A and B was accomplished in these laboratories. 10,17 These successes allowed for the synthesis of a variety of epothilone derivatives as well. We have studied the biologic effects of EA, EB, dEA and dEB on prostate cancer cell lines and found that they all inhibit growth potently ( Figure 2 and Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the total synthesis of epothilones A and B was accomplished in these laboratories. 10,17 These successes allowed for the synthesis of a variety of epothilone derivatives as well. We have studied the biologic effects of EA, EB, dEA and dEB on prostate cancer cell lines and found that they all inhibit growth potently ( Figure 2 and Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, synthesis of epothilones is now possible. 10,17,18 This will allow the generation of multiple derivatives, some of which may have increased potency, bypass resistance mechanisms or have decreased toxicity. The similar binding and biologic effects of the very dissimilar taxane and epothilone structures suggests that synthesis of derivative drugs with altered properties will be possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By far the most intriguing property of the epothilones at the in vitro level is their lack of cross resistance to MDR cell lines when compared with major antitumor agents, including paclitaxel, vinblastine, adriamycin, camptothecin, and etoposide, all of which are currently used in clinical settings (6)(7)(8)(9). The epothilones are also more watersoluble (6,(10)(11)(12)) and more readily available through chemical synthesis (6,(13)(14)(15)(16)(17)(18)(19)(20) than is paclitaxel. The solubility advantage could allow for less cumbersome administration and increased bioavailability of the chemotherapy agent than paclitaxel.…”
mentioning
confidence: 99%
“…The clinical successes of paclitaxel have spurred searches for other agents that inhibit the growth of tumors through similar tubulin-based mechanisms of action. More recently discovered compounds with a taxol-like mechanism of action include the discodermolides (4,5), eleutherobins (6), laulimalides (7), and epothilones (8)(9)(10)(11)(12)(13)(14). Despite their supposed common binding site on tubulin assemblies (15)(16)(17)(18), their chemical structures and͞or pharmacological profiles are drastically different.…”
mentioning
confidence: 99%